A companion to Nō and Kyōgen theatre (Leiden ; Boston)
2 cilt (1. c. xxxiii, 524 sayfa ; 2. c. xxxiii sayfa, sayfa [525]-1079)
Keywords: “Nō and kyōgen theatre are among the longest continuously staged dramatic forms in the world and are deeply connected to Japanese arts, culture, society, and history. This richly illustrated two-volume set brings together the important elements of these traditions to offer new insights, with contributions by Japanese and non-Japanese experts from a broad range of disciplines. It represents the most ambitious and exhaustive exploration of nō and kyōgen to date, and is an invaluable resource for both scholars and enthusiasts.” --